Transparent, Accountable and Integrity Governance of Public Bodies in West Sumatra through Increasing the Role and Function of the Regional Information Commission - Yendra, Musfi; James Bond (Dinasti Research, 2022)
Democracy means that sovereignty is in the hands of the people. Elections are a form of implementation of popular sovereignty. The people are given the freedom to choose their own leaders, both in the executive and legislature. In democracies the ruler is entrusted only part of the power of managing the state by the people. After the people are given freedom in choosing the ruler, the next stage is the involvement and participation of the people in formulating and overseeing various forms of policies born by the government,including other public bodies. Law No. 14 of 2008 concerning Public Information Disclosure is the embodiment of the substance of democracy. Especially when it comes to public information oversight. In democracies, the right to obtain public information is a human right and information disclosure is an important feature of a democratic state upholding the sovereignty of the people to realize good state administration. LawNumber 14 of 2008 concerning the Openness of Public Information has historically been motivated by the rolling out of reforms in the Unitary State of the Republic of Indonesia. Reforms that were more than a decade old at that time have brought about changes in the country's system of government. This law was passed on April 30, 2008 and came into force from 2 years of promulgation, namely on April 30, 2010. Then an Information Commission institution was formed as the implementer of this law. Both at the central and provincial and district/city levels. In West Sumatra itself, the Information Commission has been running for two periods, namely 2015-2019 and 2019-2023. Currently, the selection process for members of the Regional Information Commission of West Sumatra Province for the 2023-2027 period is being carried out. Research method with a descriptive qualitative approach.